Continuity Editing dalam Musik Video “Simpang Kiri Jalan – Kotak Itu” - Muhammad Febriansyah; Susilawati Susilawati (Jurnal Imiah Teknik Studio, 2022)
“Simpang Kiri Jalan - Kotak Itu” is a music video work that depicts the irony happened around by raising the humanist side. The implementation of continuous editing in musical works aims to create harmony in the transfer of images and the resulting work has remained aesthetic values. Editing continuity is done through cutting by narration, cutting by rhythm, and color correction techniques. The cutting by narration technique is applied so that there is continuity in the transition between audio and video by paying attention to the lyrics as outlined in the script or the lyrics uttered by the vocalist. Cutting by rhythm is applied with the aim that the image transition in line with the music beat. This can be done by firstly learning the music that will be used and finding the right beat to do the image transition. Furthermore, color correction has a function to make the color applied in every shot has continuity between one shot and another. Overall, the music video for “Simpang Kiri Jalan – Kotak Itu” has been successfully produced and edited by applying continuous editing between transitions or image transitions that match with the lyrics and the music, and has color harmony in each shot used.